Cysteine Radical/Metal Ion Adducts: A Gas‐Phase Structural Elucidation and Reactivity Study. Issue 5 (12th February 2016) - Lesslie, Michael; Lau, Justin Kai‐Chi; Lawler, John T.; Siu, K. W. Michael; Steinmetz, Vincent; Maître, Philippe; Hopkinson, Alan C.; Ryzhov, Victor
Abstract: The formation and investigation of sulfur‐based cysteine radicals cationized by a group 1A metal ion or Ag + in the gas phase are reported. Gas‐phase ion–molecule reactions (IMR) and infrared multiple‐photon dissociation (IRMPD) spectroscopy revealed that the Li +, Na +, and K + adducts of the cysteine radical remain S‐based radicals as initially formed. Theoretical calculations for the three alkali metal ions found that the lowest‐energy isomers are Cα ‐based radicals, but they are not observed experimentally owing to the barriers associated with the hydrogen‐atom transfer. A mechanism for the S‐to‐Cα radical rearrangement in the metal ion complexes was proposed, and the relative energies of the associated energy barriers were found to be Li + >Na + >K + at all levels of theory. Relative to the B3LYP functional, other levels of calculation gave significantly higher barriers (by 35–40 kJ mol −1 at MP2 and 44–47 kJ mol −1 at the CCSD level) using the same basis set. Unlike the alkali metal adducts, the cysteine radical/Ag + complex rearranged from the S‐based radical to an unreactive species as indicated by IMRs and IRMPD spectroscopy. This is consistent with the Ag + /cysteine radical complex having a lower S‐to‐Cα radical conversion barrier, as predicted by the MP2 and CCSD levels of theory. Abstract : Totally radical : Gas‐phase complexes of the cysteine thiyl radical with alkali metal ions remain tridentate (S, O, N) sulfur‐based radical species (see figure). Meanwhile, silver ions facilitate rearrangement of the thiyl radical into other isomers.